2016
DOI: 10.1186/s13018-016-0415-9
|View full text |Cite
|
Sign up to set email alerts
|

Anterior versus posterior approach in Lenke 5C adolescent idiopathic scoliosis: a meta-analysis of fusion segments and radiological outcomes

Abstract: BackgroundRadiological outcomes between anterior and posterior approach in Lenke 5C curves were still controversial. Meta-analysis on published articles to compare fusion segments and radiological outcomes between the two surgical approaches was performed.MethodsElectronic database was conducted for searching studies concerning the anterior versus posterior approach in Lenke 5C curves. After quality assessment, data of means, standard deviations, and sample sizes were extracted. RevMan 5.3 was adopted for data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 45 publications
2
32
1
1
Order By: Relevance
“…Previous studies focused on discussing the coronal plane correction between anterior and posterior surgery. Luo et al [56] reported that the posterior ASR + PSF combined anterior release and posterior fusion with instrumentation, VAT+PSF combined video assisted anterior release and posterior fusion with instrumentation without thoracoplasty, PSF posterior fusion with instrumentation without thoracoplasty, ASF anterior fusion with instrumentation and thoracotomy without thoracoplasty, VAT video assisted anterior fusion with instrumentation without thoracoplasty, W-T any scoliosis surgery with additional thoracoplasty or multiple convex rib resections, FEV1 forced expiratory volume in 1 s, FVC forced vital capacity approach can obtain a larger change of Cobb angle from pre-operation to final follow-up. Franic et al [17] found that both anterior and posterior surgeries provided a similar degree of reduction of frontal Cobb angle, and long-term effects of surgical correction on the sagittal Cobb angle seemed to be more stable in posterior group.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies focused on discussing the coronal plane correction between anterior and posterior surgery. Luo et al [56] reported that the posterior ASR + PSF combined anterior release and posterior fusion with instrumentation, VAT+PSF combined video assisted anterior release and posterior fusion with instrumentation without thoracoplasty, PSF posterior fusion with instrumentation without thoracoplasty, ASF anterior fusion with instrumentation and thoracotomy without thoracoplasty, VAT video assisted anterior fusion with instrumentation without thoracoplasty, W-T any scoliosis surgery with additional thoracoplasty or multiple convex rib resections, FEV1 forced expiratory volume in 1 s, FVC forced vital capacity approach can obtain a larger change of Cobb angle from pre-operation to final follow-up. Franic et al [17] found that both anterior and posterior surgeries provided a similar degree of reduction of frontal Cobb angle, and long-term effects of surgical correction on the sagittal Cobb angle seemed to be more stable in posterior group.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are no reported differences in blood loss, length of hospital stay and patient reported outcomes between both approaches, the posterior approach may save on the negative impacts of the anterior approach on pulmonary function. Studies also showed that the posterior-only approach has the same correction as a combined anterior/posterior spinal fusion, without the need for entering the thorax and thus negatively impacting pulmonary function [57][58][59][60][61][62][63][64][65][66][67][68][69][70][71].…”
Section: Surgical Managementmentioning
confidence: 99%
“…PCDR has the potential to preserve a distal level, as reported in some anterior procedures, and improves coronal imbalance by 52%. 35,36 A distal fusion level was saved in 2 of our 4 patients: one fused cephalad to the CEV and the other one cephalad of the touched and stable vertebrae. One patient was fused 1 level caudal to the CEV because of the presence of disc degeneration at the intervertebral disc caudal to the CEV.…”
Section: Discussionmentioning
confidence: 96%